Ultrastructure of ovarian follicular epithelium of the amazonian fish Pseudotylosurus microps (Gunther) (Teleostei, Belonidae): I. the follicular cells cycle of development - Cruz-landim, Carminda Da [UNESP]; Cruz-hofling, Maria Alice Da (Sociedade Brasileira de Zoologia, 2001)
The present paper deals with the changes on ultrastructural features of the follicular cells along the growth of the oocyte of Pseudotylosurus microps (Gunther, 1868). The epithelium pass from single squamous to pseudostratified and finally cylindric. Remarkable are the changes in the nuclear shapes, the increasing amount of rough endoplasmic reticulum and the formation of large lipid deposits in the follicular cells by the end of vitellogenic phase. Very peculiar intercellular deposits forms between the perinucleolar and vitellogenic phase of oocyte maturation. Although largely referred to in the specialized literature, our attempts to correlate the follicular cells changes with the formation of the oocyte envelopes or even with an endocrine function are not supported by conclusive evidences in the present paper.
Keywords: Pseudotylosurus microps; follicular epithelium; ultrastructure; teleost